ГРАЖДАНСКАЯ ИДЕНТИЧНОСТЬ ЛИЧНОСТИ В НОВОСТНОМ МЕДИАПРОСТРАНСТВЕ - USM ADMIN (Moldova State University, 2018)
CITIZENSHIP IDENTITY OF A PERSON IN NEWS MEDIA SPACE The present article deals with the description of citizenship identity as a type of social identity co-existing in the system of social identities. Citizenship identity model consisting of meaning content, citizenship activity and behavior in concrete situation of interaction is presented. Meaning content includes a system of citizenship values and citizenship attitudes. Psychological methods of citizenship identity research are offered taking into consideration their limitations. They include Schwartz Value Inventory, open-end statements, Color Test of Attitudes (Etkind, 1983), Citizenship Behavior Questionnaire (Zalewska & Krzywoz-Rynkiewicz, 2011), experiments. Training program of citizenship identity of a person in news media space is developed. The training is divided into two structural parts covering notions of citizenship identity and news media literacy implying reason-based trust. It is concluded that citizenship education is an important tool in formation of citizenship identity as belonging to civic society by showing values, attitudes and beha- vior patterns accepted in current civic society as a norm. News media is another powerful tool for citizenship identity formation or destruction. That is why citizenship education should include media literacy development programs in order to prevent destruction of citizenship identity by mass media. For a perspective of empirical studies, it could be especially interesting to compare results in multiethnic societies with different levels of economic prosperity, different levels of interethnic tension and peculiarities of political trust as well as taking into consideration different military situations and other threats which many states encounter at present. Keywords: citizenship identity, citizenship identity model, methods of research, media literacy, training program, trust, Ukraine.